A General Strategy Towards Encapsulation of Nanoparticles in Sandwiched Graphene Sheets and the Synergic Effect on Energy Storage. Issue 10 (11th February 2013) - Wang, Yu; Bai, Yuanjuan; Li, Xiao; Feng, Yangyang; Zhang, Huijuan
Abstract A novel and universal approach towards the unique encapsulation of nanoparticles in the sandwiched graphene sheets is presented here. In the method, a low‐cost, sustainable and environmentally friendly carbon source, glucose, is firstly applied to yield the high‐quality, uniform and coupled graphene sheets in a large scale, and the pre‐fabricated hydrated nanosheets act as the sacrificial templates to generate the enveloped metallic nanoparticles. After controllable oxidation or removal of the encapsulated nanoparticles, sandwiched nanocomposite with oxidizes nanoparticles encapsulated in graphene sheets or pure phase of sandwich‐like and coupled graphene sheets would be achieved. Moreover, the synergic effect on energy storage via Li‐ion batteries is solidly verified in the Co3O4@graphene nanocomposite. More importantly, the unique structure of the nanoparticles‐encapsulated sandwiched graphene sheets will definitely result in additional applications, such as biosensors, supercapacitors and specific catalyses. These results have enriched the family of graphene‐based materials and recognized some new graphene derivatives, which will be considerably meaningful in chemistry and materials sciences.